Creating adjoining polymorphic phase transition (PPT) regions in ferroelectric (Ba, Sr)(Zr, Ti)O3 ceramics. Issue 4 (April 2017) - Li, Yao; Cheng, Hongbo; Liu, Menglin; Zhang, Yunxiang; Yan, Peng; Wang, Chunming; Ouyang, Jun
Abstract: In this work, we report the polymorphic phase transitions(PPT) in ferroelectric Ba0.95 Sr0.05 Zr x Ti(1- x ) O3 (BSZT, x  = 0.01–0.10) ceramics synthesized by using a solid-state reaction method. The doping elements and composition ratios were selected to create adjoining PPT phase boundaries near room temperature, hence to achieve a broadened peak of piezoelectric performance with respect to composition. The temperature-composition phase diagram was constructed and the effects of PPT on the electromechanical and ferroelectric properties of the ceramics were investigated. It was revealed that the two adjacent PPT regions at room temperature showed different characteristics in property enhancement. However, due to the proximity of the phase boundaries, Ba0.95 Sr0.05 Zr x Ti(1- x ) O3 ceramics in a fairly broad range of compositions (0.02 ≤  x  ≤ 0.07) showed excellent piezoelectric properties, including a large piezoelectric constant (312 pC/N ≤  d 33  ≤ 365 pC/N) and a high electromechanical coupling coefficient k p (0.42 ≤  k p  ≤ 0.49).